INFLUENCE OF INTERNET OF THINGS ON PUBLIC SPACES CREATION PRINCIPALS AND FURNISHING - Kokorska, Maria (Innovation in Woodworking Industry and Engineering design, 2024)
The paper reviews the influence of modern technology – Internet of things (IOT) on the public environment. Different aspects of this influence on the principals of how the spaces function, how they are designed and furnished are studied. The leading trends in these principals, initiated by the penetration of IOT technology are shown, as human centric lighting and heating, smart furniture etc. All these are leading to energy saving, increased security, productivity and comfort enhancement.